EFFECTIVENESS OF METHODS FOR TREATING INTRA-ARTICULAR FRACTURES OF THE DISTAL END OF THE THIGH BONE (World Bulletin of Public Health, 2024)
To study the comparative results and evaluate the effectiveness of osteosynthetic methods used in intra-articular fractures
Keywords: skeletal; evaluate; comparative